Development of Interactive E-Book Based on Book Creator to Improve Creativity of Vocational High School Students - Hendro Eko Handoko; Eges Triwahyuni; Kustiyowati Kustiyowati (Postgraduate, University of Mataram, 2025)
This study was conducted at SMKN to address the lack of media variation in vocational education and to improve student creativity, especially in the Computer and Network Engineering (TKJ) major. The objective was to develop an interactive e-book based on Book Creator and examine its development process and effectiveness. The research used the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) within the R&D framework. Instruments included expert validation sheets, student response questionnaires, pretests, posttests, and observation forms. The developed media presented learning content with interactive features such as text, audio, video, animations, and quizzes. Results showed that media validation scored 92%, material 91.01%, student response 97.9%, and pretest-posttest instrument validity over 90%. The e-book effectively increased students’ creativity: fluency improved from 62.1 to 83.4 (N-Gain 0.56), originality from 58.9 to 81.7 (N-Gain 0.53), flexibility from 60.5 to 85.0 (N-Gain 0.61), and elaboration from 64.0 to 84.5 (N-Gain 0.58). The overall N-Gain score was 0.58 (medium category). A paired t-test (p = 0.000 < 0.05) confirmed significant improvement. Student and teacher responses also indicated the media was enjoyable, easy to use, and facilitated concept understanding. In conclusion, the Book Creator-based interactive e-book is valid, practical, and effective in fostering creativity among vocational students and supports 21st-century learning.